EVALUATION OF MANAGEMENT SYSTEM OF MEDICAL AND BIOMEDICAL WASTES AT WAD MEDANI TWON, SUDAN - Fedlel-Moula, Musa M.; Elhassan, Abdelellah M.; Idris, Ali Ahmmed (مجلة الجزيرة للعلوم الصحية; مجلد 5 عدد 2 (2009), 2009)
This study was conducted at Wad Medani Town, Gezira state , Sudan to evaluate quantitatively and qualitatively the medical and biomedical waste (MBMW) generated by the Healthcare Establishments (HCEs).The study was conducted by the inventory of all HCEs by category, followed by site visits, developing a questionnaire, determining the sample size, quantifying the (MBMW) and analyzing the collected data. The study showed that, there was no appropriate technical management system for the management of MBMW at Wad Medani town. The waste managed as domestic waste, all mixed together, collected, handled, stored, transported and finally, disposed of. The results showed that, the total amount of non-health risk solid waste (NHRSW) generated per day was 399.59 Kg (92% of these wastes were produced by Wad Medani Teching Hospital. While the total average amount of Health Risk Solid Waste (HRSW) generated per day was 265kg.The total amount of Health Risk Liquid Waste (HRLW) generated per day was 148 litre ( 93% arising from Wad Medani Teaching Hospital . The study recommended that, it is very important to establish an adequate management system for (MBMW) in all (HCEs) in Wad Medani town, accompanied with appropriate management planning copes with existing economics, social and environmental conditions.The importance of training, awareness and education of all medical staff , workers and for those who deal with and come in contact with (MBMW) on how to deal with them to protect their health and safety.